Biological data mining in protein interaction networks - Li, Xiao-Li, 1969-; Ng, See-Kiong (Medical Information Science Reference, 2009)
"The goal of this book is to disseminate research results and best practices from cross-disciplinary researchers and practitioners interested in, and working on bioinformatics, data mining, and proteomics"--Provided by publisher.